The becoming of a Prehistoric Landscape: Palaeolithic Occupations and Geomorphological Processes at Lojanik (Serbia) - Lesage, Camille (2022)
Accomplishing long-term plans to harvest and modify natural resources has been a crucial skill for the survival of our species since early Prehistory. Research on this first step of production mostly focuses on the provenience study of lithic artifacts uncovered at archaeological sites, using petrographic and geochemical analyses to correlate the artifacts with potential geological outcrops. Although fundamental for understanding key aspects of landscape use and mobility, regional raw material economy, and extraction technology, Palaeolithic raw material sources have been less intensively investigated, as they are often difficult to locate and challenging to tackle with traditional archaeological approaches. Lojanik in the Central Balkans is one of the largest Prehistoric quarrying areas known in Europe, showing numerous lithic raw material outcrops exploited from the Middle Palaeolithic to the Chalcolithic periods, over an area of 18 hectares. In this paper, we present the results from our renewed research program in this region. Combining airborne LIDAR mapping, geomorphological and archaeological survey, and techno-typological analysis of lithic artifacts, we were able to reconstruct the geomorphological evolution of the landscape and its use by prehistoric societies.